Redistribution of Platelet Glycoproteins Induced by Allo- and Autoantibodies - Santoso, S; Kiefel, V; Mueller-Eckhardt, C (Thrombosis and Haemostasis, 1987)
The redistribution of platelet glycoproteins (GP) Ib, IIb and IIIa in response to stimulation with human platelet specific alloantibodies, autoantibodies and a quinidine-dependent antibody was investigated using immunofluorescence and a quantitative radioimmunoassay. The platelet GPs carrying the corresponding epitopes were determined using immunoblot technique or radioimmunoprecipitation. In accordance with previous results obtained with murine monoclonal platelet specific antibodies, redistribution upon stimulation with human platelet reactive antibodies was observed only due to reactions with epitopes on GP IIb, IIIa, respectively, but not on GP Ib. We therefore believe that membrane redistribution of human platelets induced by various antibodies is a function of the GP recognized by those antibodies rather than the source of the platelet reactive antibody.
Keywords: Platelet glycoprotein; Platelet specific antibodies; Redistribution; Endocytosis